2015
DOI: 10.12720/jomb.4.2.135-138
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Short Term Meditation on Brain-Computer Interface Performance

Abstract: Brain-Computer Interface (BCI) systems is a direct communication pathway between the brain and an external device. BCI systems enable patients with severe neuromuscular disorders to use their brain signal to communicate with others. BCI users need to maintain stable mental states to achieve a higher accuracy rate, while distraction and frustration will degrade the performance. Research had found that long-term mindfulness meditation practice can help increase regulate the mental state, and thus enhance the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 7 publications
1
6
0
Order By: Relevance
“…A study by Jiang et al (2021) however found that participants with long-term training in meditation had more stable resting EEG mu rhythms, better resting state SMR predictors than nonmediators, achieved larger control signal contrasts in the motor imagery tasks and fewer subjects in the mediating group were BCI illiterates. For short-term and long-term effects of meditation training interventions on BCI performance testing of healthy users see Tan et al (2014) or Tan et al (2015). These latter results corroborate the finding that neurophysiological correlates obtained from the analysis of a user's mental state during rest (e.g., Blankertz et al, 2010) are reliable predictors of BCI performance.…”
Section: Role Of Assessment Methodssupporting
confidence: 67%
“…A study by Jiang et al (2021) however found that participants with long-term training in meditation had more stable resting EEG mu rhythms, better resting state SMR predictors than nonmediators, achieved larger control signal contrasts in the motor imagery tasks and fewer subjects in the mediating group were BCI illiterates. For short-term and long-term effects of meditation training interventions on BCI performance testing of healthy users see Tan et al (2014) or Tan et al (2015). These latter results corroborate the finding that neurophysiological correlates obtained from the analysis of a user's mental state during rest (e.g., Blankertz et al, 2010) are reliable predictors of BCI performance.…”
Section: Role Of Assessment Methodssupporting
confidence: 67%
“…Short term meditation training is known to improve attention and self‐regulation [78], and experienced meditators show more distinguishable EEG patterns than untrained subjects during motor imagery tasks [79]. Thus, mindfulness meditation training may help increase the degree of concentration and improve signal‐to‐noise ratios and thereby facilitate MI‐BCI control performance Previous studies have confirmed that MI‐BCI control accuracy could be improved by both long term (12 weeks) and short term (4 weeks) mindfulness meditation practice [80, 81]. Based on the above results, we can infer that MI‐BCI inefficient subjects, particularly category Ⅰand Ⅱ subjects, may benefit from mindfulness meditation practice.…”
Section: Solving the Mi‐bci Inefficiency Problemmentioning
confidence: 99%
“…With growing evidence suggesting that meditation brings enhanced attention and brain rhythm control, it is reasonable to hypothesize that people with meditation experience would develop a better ability to control SMR-based BCI. Indeed, previous work has investigated the effect of meditation on SMR BCI cursor control ( Cassady et al, 2014 ; Tan et al, 2014 , 2015 ; Kober et al, 2017 ; Stieger et al, 2020 ) or just generating ERD/ERS without controlling a BCI system ( Kerr et al, 2011a , b , 2013 ; Rimbert et al, 2019 ). Similar to what Tang et al (2015) summarized for the neuroscience aspect of meditation studies, efforts to study the meditation effect on SMR BCI could be divided into two categories, longitudinal studies and cross-sectional studies:…”
Section: Introductionmentioning
confidence: 99%
“…Previous longitudinal studies separated meditation-naïve subjects into a meditation group and a control group, with the meditation group receiving meditation training and the control group receive either active control tasks or no specific task ( Mahmoudi and Erfanian, 2006 ; Tan et al, 2014 , 2015 ; Botrel and Kübler, 2019 ; Stieger et al, 2020 ). After that, BCI performance and/or neurophysiological difference between the two groups was assessed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation